Assessment of the traffic - Freitas, E. (2010)
Traffic noise is an important branch of the environment pollution which deeply affects the population and for that reason it has been included in the set of pavement performance indicators. Nevertheless, the knowledge on the environmental impact of the existing surface pavement layers is very limited, particularly for what respects to tyre/road noise of thin layers. These layers are at the present time widely used in a great extent with rubberized asphalt both in urban and rural roads especially in the north of Portugal due to environmental concerns. In this paper the comparison of the tyre/road noise (Lmax) generated in roads with thin surface layers is made. The noise levels generated by light and heavy vehicles are set according to the Statistical Pass-By Method (SPB) of which test methods is described in the standard ISO 11819-1:1997. At management level the information provided by tyre/road noise tests is essential to support environmentally sustainable construction and maintenance alternatives. Furthermore, at project level, the results give some insight about the relation surface layers/traffic composition.